Work in progress: germinal requirement in implementing an android, inquiry-based application in science education (AIBASE) - Kamal Ruzaman, Nazirah; Rosli, D’oria Islamiah (American Scientific Publishers, 2018)
Inquiry-based learning is a teaching and learning method that support an active learning environment by enhancing the students’ capabilities to solve problems using critical thinking skills. Recently, information technology verifiably widely spreading learning model in the 21st -century education by contributing in enhancing students’ learning motivation. This study aims at initializing requirements for developing an android application based on the inquiry-based method in terms of the most suitable inquiry-based method that can be embedded into the application, based on inquiry components. This research draws upon literature review and screening of ten educational android applications. This research will provide valuable information regarding the suitable inquiry-based method that can be embedded through the implementation of educational android application